The challenges in enforcing post divorce orders of native courts in East Malaysia - Ambaras Khan, Hanna; Abdul Hak, Nora; Mohd Zin, Najibah; Che Soh, Roslina (International Islamic University Malaysia, 2021)
The native court in Malaysia comprises of Mahkamah Anak Negeri Sabah and Mahkamah Bumiputera Sarawak. The existence of this court is recognised by the Malaysian Government and they are mentioned in the Federal Constitution of Malaysia. Although these courts are given power and authority in dealing with the personal law of natives in each state, there are challenges in enforcing post-divorce orders made by these courts. This article is significant since there is a dearth of study on this topic. The main objective of this article is to examine the enforcement of post-divorce orders of native courts within East Malaysia. It will also explore the problems and challenges of divorcees in enforcing divorce orders and provide recommendations to improve the existing system. This article adopts library-based and qualitative research method which consists of group discussions and interviews with the village headman (ketua kampung), headman (penghulu), community leader, native courts’ judges, native court of appeal’s judge, registrar of native court and several divorcees. The result of this research identified four challenges vis-a-vis: the capability to find the husband upon the issuance of the divorce order; second, husband’s default payment of maintenance; lack of manpower in enforcing the order and lastly, husband’s conversion to Islam. Thereafter, this article suggests that the government could provide assistance by empowering court bailiffs or enforcement bodies, increasing funding and to designate a special department for enforcement of divorce orders.